Asuhan Keperawatan Pada Pasien Dengan Diabetes Melitus Tipe 2 - Dilla Rachmatul Khoir; Hertuida Clara (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2019)
Diabetes mellitus is a group of metabolic diseases characterized by increased glucose levels in the blood due to defect in insulin secretion, insulin action, or both. According to the World Health Organization (WHO) in 2016, diabetes mellitus is among the top 10 causes of death in the world. Clinical manifestations of Diabetes mellitus according to Black and Hawks (2014), have three characteristics, namely: polyuria, polyphagia, polydipsy, with complications that can occur in the form of microvascular and macrovascular complications. The purpose of this paper is to get real experience in providing nursing care to Diabetes Mellitus patients. The method used in writing scientific papers is descriptive method. The results of nursing care obtained are: for clinical manifestations, which are found in cases are polyuria, polydipsia, polyphagia, decreased BB, weak and tired. Of the seven nursing diagnoses in theory, there are two nursing diagnoses that appear in cases where the risk of nutritional changes is less than the body's needs related to insulin deficiency, nausea; Fatigue is associated with decreased metabolic energy production. At the implementation stage of nursing, of the five nursing diagnoses in this case, everything has been done so that there are no gaps. At the nursing evaluation stage, of the five nursing diagnoses in this case, there is one nursing diagnosis that can be overcome, namely excess fluid volume is associated with decreased kidney function, water retention.